MOTIVASI DAN KINERJA PENYULUH TERHADAP PETANI KARET DI KABUPATEN KAMPAR - Rosnita Rosnita (Universitas Lancang Kuning, 2016)
Rubber is one of the commodities in the plantation sector that are excellent in Riau after palm oil. It is evident from the many areas in Riau Province that is potentially in the development of the rubber. Kampar Regency as well as largerst rubber producer after Kuantan Singingi Regency, Kampar Regency in 2013 is capable of producing as much as 78.031 tons of rubber with rubber land area of 101.597 Ha. Only from year to year the number of existing rubber farmers diminishing due to the transfer of commodities into palm oil. In thins case required the efforts of extension to change the mindset of farmers as well as the skills, attitudes and income of farmers through extension activities. In this case, the motivation factor is considered to affect the success of extension activities that have an impact on performance achieved. Motivation extension seen from the internal and exsternal factors while the performance is measured extension of the preparation, implementation and evaluation. Method used is primarily to survey the number of respondents as 6 extension taken from one of the districts in which Kampar Regency is Kampar Kiri. Analysis used technique likert’s scale. The results obtained by motivation of overall extension categorized fairly, where in the internal factors have been categorized as high, while external factors is still considered. Performance of extension categorized good at preparatory stage, while there are enough categories at stage of implementation and evaluation. But overall performance of extension workers categorized good in the Kampar Regency